Karya Tulis Ulama’ Nusantara Dan Relevansinya Dalam Perkembangan Pendidikan - Hairul Puadi; Kurdi (Pascasarjana Institut Agama Islam Al-Qolam, 2020)
In this study the plurality and diversity between people and nations within the framework of human unity, this philosophy creates Islamic civilization with moderate characteristics, harmonizing the individual uniqueness of each people and nation, with the virtues or badness that occurs in all people. and nation. So, what happens then is a sense of pride in the uniqueness and virtues that are owned without denying other specialties and strengths. This attitude appears in Islamic civilization. So, it can defeat the tendency of non-Arab fanaticism and the fanaticism of the Arabs as a whole. An interesting study of Islam Nusantara is a platform to reaffirm that Islam in this country adapts local values ??that characterize it. The legacy of the ulama has become an important part of the Islamic scientific transformation of the archipelago.